Method for estimating future markets for high-temperature superconducting power devices. - Sheahen, T.P (IEEE Transactions on applied superconductivity)
This paper describes a spreadsheet model for estimating the impact of high-temperature superconducting (HTS) power devices on the national electric grid. The distribution of losses in the national grid is carefully traced and those losses that HTS can eliminate are identified. The energy savings achievable by the many sizes of HTS generators, transformers, cables, and motors are then computed and totaled using a spreadsheet analysis. The economic savings are very sensitive to the price (and Je) of HTS wire, and to the cost of cooling the devices to operating temperature. A market penetration model is used to estimate how fast HTS devices become commercially,successful. The emphasis of the paper is the analytic tool, not the numerical results of one specific case. This entire model is explicitly designed to allow others to enter their own estimated parameters and arrive at their own conclusions.